Biochemical characterisation of NS2B-NS3 protease from flaviviruses - Nah, Jojo Qian Hui (2016)
Dengue virus (DENV) infection affects millions of people in the world. DENV, the causal agent is a member of the flavivirus genus. The virus is transmitted by mainly Aedes aegypti mosquito. Despite bringing adverse effects to the health and economy of the society, there is no effective antiviral against DENV. The virus genome encodes for seven non-structural (NS) proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5) and three structural proteins (envelope (E), capsid (C), membrane (M). Among the viral proteins, non-structural protein 3 (NS3) is a multi-functional protein, which the N-terminal domain comprised of a chymotrysin- like serine protease (NS3pro), responsible for viral polyprotein cleavage. In order to fold properly and become active, NS3pro requires the interaction with 47 amino acids central hydrophilic portion of its cofactor, NS2B. Hence, NS2B-NS3pro is seen as a potential drug target for antiviral therapy. In the dengue research field, the hydrophilic portion of NS2B is often engineered to NS3pro domain by joining with a flexible linker of nine amino acids, Gly4-Ser-Gly4 in studying their properties. Here, we compared the enzymatic activities of DENV NS2B47- G4SG4 NS3 Wild Type (WT) pro, DENV NS2B47- G4SG4 NS3WTSSpro with DENV NS2B47- G4SG4 NS3WTSS and Zika virus (ZIKV) NS2B-NS3 WT pro. We reported that ZIKV NS2B-NS3 WTpro has the highest protease activity and DENV NS2B47- G4SG4 NS3WTpro has the highest rate of trans-cleavage. These findings demonstrate the importance of protease activity that could be used for drug discovery process in designing inhibitor.